Incêndios em vegetação na cidade de João Pessoa-PB - Silva, Pablo Raphael Oliveira Honorato da (2021)
The occurrence of fires in vegetation, especially in urban areas, can be directly related to the climatic conditions of a given region, as well as to anthropogenic factors. However, verifying the causes and consequences of fires in vegetation in urban areas, becomes a great challenge due to the complexity of anthropic and natural factors that can trigger such a process. In the last years, the city of João Pessoa / PB has presented a significant incidence of fires in vegetation distributed by its urban network in different locations, generating a series of socio-environmental consequences. In this context, there is a need to analyze the factors associated with vegetation fires in the city of João Pessoa / PB, which has become the general objective of this work. To carry out the study, a bibliographic review was initially carried out regarding the subject in question and a quantitative and documentary research. Data were collected on the characteristics of fire occurrences in vegetation in the city of João Pessoa \ PB and its distribution, using the database of the Military Fire Brigade of Paraíba, from a historical series corresponding to the years 2012 to 2019. To find out the possible influence of natural causes (climatological variables), the following daily data from the National Institute of Meteorology were collected: average, maximum and minimum temperature; average and minimum relative humidity; average wind speed and maximum gust; total precipitation; average atmospheric pressure and dew point. Such data were collected for the same time series of vegetation fires in the city of João Pessoa / PB (2012 to 2019). In order to assess the possible influence of anthropogenic causes for the occurrence of fires in vegetation in the study area, data on the occupation of land in the studied area were tabulated and specialized, based on data from the City Hall. The results show the highest number of occurrences of vegetation fires in the city of João Pessoa / PB between the years 2015 and 2016, in which El Niño phenomena were recorded, classified as “very strong”, thus suggesting a cause relationship and effect between these processes. The months of November and December (the driest period in the region) had the highest occurrence rates in the evaluated time series and the predominant times of occurrences are between 13 and 18 hours of the daily cycle. It was also found that the neighborhoods with the highest rates of occurrence in vegetation fires in the city of João Pessoa / PB are: Mangabeira, Altiplano and Cabo Branco, and that the occurrences tend to have a higher incidence in the neighborhoods with the highest demographic density.